Crystallization and hydrogen absorption in a Ni32Nb28Zr30Fe10 melt spun alloy and correlation with icosahedral clusters. (28th February 2022) - Trequattrini, Francesco; Brutti, Sergio; Palumbo, Oriele; Hulyalkar, Madhura; Mushongera, Leslie T.; Ye, Wenye; Khan, M. Rashed; Dolan, Michael; Chandra, Dhanesh; Paolone, Annalisa
Abstract: The crystallization and the hydrogen absorption properties of a Ni32 Nb28 Zr30 Fe10 melt spun ribbon were investigated. X-ray diffraction measurements reveal that a small fraction of the ribbon is in a crystalline state, whereas the main component is amorphous. The bulk crystallization process of the alloy ribbon occurs in two steps above 770 K, as measured by differential scanning calorimetry. At each step of the crystallization process, an unusually low activation energy of the order of 180 kJ/mol, was observed. Hydrogen absorption pressure-composition isotherms measured between 598 K and 673 K showed that the enthalpy of hydrogenation is quite high (∼85 kJ/mol), as compared to that of analogous ribbons. The isotherms of these ribbons do not exhibit any plateau, similarly to other amorphous materials, but they exhibited extremely slow kinetics for hydrogen absorption. To simulate the local atomic structure involving cluster formation in amorphous Ni32 Nb28 Zr30 Fe10 alloy, DFT-MD approach was used to construct an amorphous supercell of this alloy with 108 atoms. Calculations predicted that a fully amorphous structure of Ni32 Nb28 Zr30 Fe10 can form. The low activation energy of crystallization observed before hydrogenation is due to the presence of only 3 full icosahedra without any Ni-centered icosahedra, that could provide resistance against crystallization. Moreover, a cluster analysis of the Ni32 Nb28 Zr30 Fe10 alloy after hydrogenation showed interaction of hydrogen atoms with only two icosahedra out of four found in this case, and this could be the probable reason for the extremely slow kinetics of hydrogen absorption. Graphical abstract: Image 1 Highlights: Melt spun Ni32 Nb28 Zr30 Fe10 is mainly amorphous with a minor crystalline inclusion. Activation energy for crystallization is extremely low (180 kJ/mol). Large quantities of hydrogen are stored with a slow kinetics. DFT Molecular Dynamics show the alloy has poor resistance to crystallization. Hydrogen interacts with two out of four icosahedral clusters with a slow kinetics.